Loss of lipin 1‐mediated phosphatidic acid phosphohydrolase activity in muscle leads to skeletal myopathy in mice. Issue 1 (20th July 2018) - Schweitzer, George G.; Collier, Sara L.; Chen, Zhouji; Mccommis, Kyle S.; Pittman, Sara K.; Yoshino, Jun; Matkovich, Scot J.; Hsu, Fong-Fu; Chrast, Roman; Eaton, James M.; Harris, Thurl E.; Weihl, Conrad C.; et al.
ABSTRACT: Lipin 1 regulates glycerolipid homeostasis by acting as a phosphatidic acid phosphohydrolase (PAP) enzyme in the triglyceride‐synthesis pathway and by regulating transcription factor activity. Mutations in human lipin 1 are a common cause of recurrent rhabdomyolysis in children. Mice with constitutive whole‐body lipin 1 deficiency have been used to examine mechanisms connecting lipin 1 deficiency to myocyte injury. However, that mouse model is confounded by lipodystrophy not phenocopied in people. Herein, 2 muscle‐specific mouse models were studied: 1 ) Lpin1 exon 3 and 4 deletion, resulting in a hypomorphic protein without PAP activity, but which preserved transcriptional coregulatory function; and 2 ) Lpin1 exon 7 deletion, resulting in total protein loss. In both models, skeletal muscles exhibited a chronic myopathy with ongoing muscle fiber necrosis and regeneration and accumulation of phosphatidic acid and, paradoxically, diacylglycerol. Additionally, lipin 1–deficient mice had abundant, but abnormal, mitochondria likely because of impaired autophagy. Finally, these mice exhibited increased plasma creatine kinase following exhaustive exercise when unfed. These data suggest that mice lacking lipin 1–mediated PAP activity in skeletal muscle may serve as a model for determining the mechanisms by which lipin 1 deficiency leads to myocyte injury and for testing potential therapeutic approaches.—Schweitzer, G. G., Collier, S. L., Chen, Z., McCommis, K. S., Pittman, S. K., Yoshino, J., Matkovich, S. J., Hsu, F.‐F., Chrast, R., Eaton, J. M., Harris, T. E., Weihl, C. C., Finck, B. N. Loss of lipin 1–mediated phosphatidic acid phosphohydrolase activity in muscle leads to skeletal myopathy in mice. FASEB J. 33, 652–667 (2019). www.fasebj.org